2016
DOI: 10.22494/cot.v4i2.64
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional characteristics of cryopreserved multipotent mesenchymal stromal cells from bone marrow, adipose tissue and tendons

Abstract: The aim of study was to comparatively evaluate the morphological and functional properties of cryopreserved multipotent mesenchymal stromal cells (MMSCs) from bone marrow, fat and tendon.Materials and methods. MMSC cultures obtained from rat bone marrow, fat and tendon. The cells was cryopreserved under protection of 10 % DMSO and 20% FBS with cooling rate of 1 deg/min down to -80°C followed by plunging into liquid nitrogen. In the studied cultures the membrane integrity, immunophenotype, ability to colony for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
(26 reference statements)
0
6
0
1
Order By: Relevance
“…Primary suspension of cells from biopsies of adipose and cartilage tissues of rats (n = 5) was obtained by enzymatic digestion (Volkovа et al, 2016). To do this, tissue samples were washed with Hanks' solution (PAA, Austria) with gentamicin (150 μg/mL) (Farmak, Ukraine) and incubated in a type II collagenase solution (1.5 mg/mL) (PanEco, Russia) at 4 °C for 18 hours.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary suspension of cells from biopsies of adipose and cartilage tissues of rats (n = 5) was obtained by enzymatic digestion (Volkovа et al, 2016). To do this, tissue samples were washed with Hanks' solution (PAA, Austria) with gentamicin (150 μg/mL) (Farmak, Ukraine) and incubated in a type II collagenase solution (1.5 mg/mL) (PanEco, Russia) at 4 °C for 18 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Cell cultures derived from all studied sources have phenotype of precursor cells of mesenchymal origin. The MMSCs of cartilage tissue are characterized by a greater capacity for colony formation and proliferation, and lower capacity for directed differentiation than MMSCs from bone marrow and adipose tissue (Volkovа et al, 2016). In another previous study (Volkovа et al, 2019) we investigated the effect of growth and differentiation factors on CrMMSCs from bone marrow, adipose and cartilage tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Раніше нами було показано, що клітинні культури отримані з кісткового мозку та альтернативних джерел, -сухожильної та жирової тканин, -мають імунофенотип клітин попередників мезенхімального походження [14], зберігають здатність до проліферації, міграції та синтезу колагену І типу [15].…”
Section: вступunclassified
“…Therefore, the study of the characteristics of cryopreserved cultures is an important trend in modern biotechnology. In previous studies, we investigated the morphofunctional characteristics of cryopreserved MMSCs obtained from the bone marrow, adipose and tendon tissues, and found that adipose tissue-derived MMSCs (AT-MMSCs) had a greater ability to colony formation, proliferate, and have the same ability to direct differentiation compared with MMSCs from bone marrow [20].…”
mentioning
confidence: 99%